A counting intervention promotes fair sharing in preschoolers. Issue 5 (27th April 2022) - Chernyak, Nadia; Harris, Paul L.; Cordes, Sara
Abstract: Recent work has probed the developmental mechanisms that promote fair sharing. This work investigated 2.5‐ to 5.5‐year‐olds' ( N  = 316; 52% female; 79% White; data collected 2016–2018) sharing behavior in relation to three cognitive correlates: number knowledge, working memory, and cognitive control. In contrast to working memory and cognitive control, number knowledge was uniquely associated with fair sharing even after controlling for the other correlates and for age. Results also showed a causal effect: After a 5‐min counting intervention (vs. a control), children improved their fair sharing behavior from pre‐test to post‐test. Findings are discussed in light of how social, cognitive, and motivational factors impact sharing behavior.